2021
DOI: 10.4081/aiua.2021.2.189
|View full text |Cite
|
Sign up to set email alerts
|

Obesity rates in renal stone formers from various countries

Abstract: Objective: To collect evidence on the rate of obesity in renal stone formers (RSFs) living in different climatic areas and consuming different diets. Materials and methods: Data of adult renal stone formers were retrospectively collected by members of U-merge from 13 participant centers in Argentina, Brazil, Bulgaria (2), China, India, Iraq (2), Italy (2), Nigeria, Pakistan and Poland. The following data were collected: age, gender, weight, height, stone analysis and procedure of stone removal. Results: In tot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…evaluated the obesity rate (measured by BMI) of renal stone formers from different countries ( N = 10). In their study, Chinese renal stone patients had the lowest obesity rate (2%), and the obesity rate in Chinese renal stone formers was not higher than the obesity rate in general Chinese population [ 18 ]. In a cross-sectional study of 10,281 Chinese rural participants, Fan et al.…”
Section: Discussionmentioning
confidence: 99%
“…evaluated the obesity rate (measured by BMI) of renal stone formers from different countries ( N = 10). In their study, Chinese renal stone patients had the lowest obesity rate (2%), and the obesity rate in Chinese renal stone formers was not higher than the obesity rate in general Chinese population [ 18 ]. In a cross-sectional study of 10,281 Chinese rural participants, Fan et al.…”
Section: Discussionmentioning
confidence: 99%
“…Nephrolithiasis represents a common disorder with a lifetime cumulative incidence of 5–10% and a progressively increasing prevalence worldwide [ 1 , 2 ], affecting all ages, sexes, and races, but frequently occurring between the 2nd and 4th decades of life [ 3 ]. Lithogenesis is characterized by an imbalance between the solubility and precipitation of minerals in the urine influenced by several factors, including climate, social-economic status, eating habits, obesity, genetic inheritance, and metabolic disorders [ 2 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 ]. It is well established that stone formers (SF) exhibit a reduction of bone mineral density (BMD) [ 12 , 13 ], which may be exacerbated under low calcium intake [ 14 ], and histomorphometric studies have reported low bone formation and increased bone resorption [ 15 , 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%